2008
DOI: 10.7863/jum.2008.27.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Sonographic and Clinical Characteristics as Predictors of Ovarian Torsion

Abstract: Objective. The purpose of this study was to determine the most closely associated sonographic and clinical characteristics of ovarian torsion. Methods. The medical records and sonographic studies of 39 patients with pathologically proven ovarian torsion diagnosed at our institution from July 1, 2000, through December 31, 2005, were retrospectively reviewed. The volumes of the affected ovaries and ovary/mass complexes were compared with an age-appropriate standard. Statistical significance of the data was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
94
1
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(110 citation statements)
references
References 20 publications
8
94
1
7
Order By: Relevance
“…Furthermore, we were unable to identify a significant difference in the frequency of acute abdominal pain when compared between patients with and without ovarian torsion (P = 1.00). Although most laboratory findings are normal in patients with ovarian torsion, some studies have identified a minor degree of leukocytosis in 27%-50% of patients (12,13). In the present study, only 20% of the patients with ovarian torsion exhibited leukocytosis, and no statistical difference was found in the frequency of leukocytosis when compared between patients with and without ovarian torsion (P = 1.00).…”
Section: Discussioncontrasting
confidence: 41%
“…Furthermore, we were unable to identify a significant difference in the frequency of acute abdominal pain when compared between patients with and without ovarian torsion (P = 1.00). Although most laboratory findings are normal in patients with ovarian torsion, some studies have identified a minor degree of leukocytosis in 27%-50% of patients (12,13). In the present study, only 20% of the patients with ovarian torsion exhibited leukocytosis, and no statistical difference was found in the frequency of leukocytosis when compared between patients with and without ovarian torsion (P = 1.00).…”
Section: Discussioncontrasting
confidence: 41%
“…The use of Doppler ultrasound also helps in the diagnosis to a great extent. Shadinger et al, [9] in a retrospective study of 39 adnexal torsion cases found a positive predictive value of 94% for the doppler finding of absent venous flow. The sonographic findings which may predict adnexal torsion are visualisation of a cystic, solid or complex mass at the location of the adnexal, cranial to the uterine fundus, thickening of the adnexal wall, unilateral ovarian enlargement, peripherally enlarged follicles, cystic hemorrhage and free pelvic fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Adnexal torsion is considered to be a difficult diagnosis before surgery, and the correct diagnosis is made in only less than half of the cases. 15 Because of the nonspecific signs and symptoms associated with ovarian torsion, a high index of suspicion is required when deciding whether to intervene surgically. 8 As the presenting symptoms and signs in postmenopausal women are indefinite and nonspecific, the diagnosis of adnexal torsion is not often considered.…”
Section: Discussionmentioning
confidence: 99%